EFEKTIVITAS PERENDAMAN BENIH DENGAN AIR KELAPA UNTUK MENINGKATKAN KUALITAS BENIH PADI YANG DISIMPAN - Ego, Ego (Enviagro: Jurnal Pertanian dan Lingkungan, 2025)
Increasing rice productivity can be done by using quality seeds. One effort to improve the quality of rice seeds is by invigoration using organic materials such as coconut water. This research aims to determine the viability and vigor of rice seeds by soaking in coconut water and to find out which concentration of coconut water is best for increasing the viability and vigor of rice seeds. Research was conducted at the Agrotechnology Seed, Universitas Bangka Belitung. The research used a completely randomized design consisting of three treatment levels of coconut water concentration, namely control (K0), 50 ml young coconut water (K50) and 100 ml young coconut water (K100), each treatment was repeated 5 times so that there were 15 units. test. The data was subjected to analysis of variance (Anova) and further tests were carried out DMRT (Duncan Multiple Range Test) 95% confidence level. The results of the analysis showed that the coconut water concentration treatment showed results that had a very significant effect on the variable seed growth rate (KCt) and had no significant effect on the variables germination capacity, maximum growth potential and vigor index. The research results showed that immersion in young coconut water with a concentration of 50 ml had the best effect on growth speed (Kct). 100 ml concentration gave the highest results in terms of germination, maximum growth potential and vigor index but was not much different from other treatments.